2020
DOI: 10.1016/j.physa.2019.123093
|View full text |Cite
|
Sign up to set email alerts
|

Global crises and gold as a safe haven: Evidence from over seven and a half centuries of data

Abstract: Using annual data spanning the period of 1258-2018, we test the safe haven characteristic of gold in the wake of global crises. We find that, when we allow for regime-switching to capture nonlinearity and structural breaks, gold serves as a strong hedge against crises, especially during the bullish regime of the market, and in particular from the post-World War I period, as suggested by a time-varying model. In comparison, silver, however, does not seem to possess the safe haven property over the historical pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 22 publications
(15 reference statements)
0
26
0
Order By: Relevance
“…The results from the Markov switching model indicate gold returns have high probability of staying in the first volatility than the second volatility regime. The rise in gold price reflects investor uncertainty in the market, however, gold is a stronger hedge commodity in global financial crises or risks, especially when gold market is performing and trading at higher prices ( Boubaker et al, 2020 ). Our findings are consistent with studies that suggest crisis tend to negatively affect gold price, but to lesser extent, compared to similar safe-haven precious metal ( Huang and Kilic, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results from the Markov switching model indicate gold returns have high probability of staying in the first volatility than the second volatility regime. The rise in gold price reflects investor uncertainty in the market, however, gold is a stronger hedge commodity in global financial crises or risks, especially when gold market is performing and trading at higher prices ( Boubaker et al, 2020 ). Our findings are consistent with studies that suggest crisis tend to negatively affect gold price, but to lesser extent, compared to similar safe-haven precious metal ( Huang and Kilic, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The major shortcoming of these studies is their focus on a specific crisis, such as the financial/stock market crisis (Ciner et al, 2013;Gutiérrez et al, 2013;Dee et al, 2013;He, et al, 2018;Iqbal, 2017;, debt crisis (Agyei-Ampomah et al, 2014;Bredin et al, 2015;Boubaker et al, 2020), exchange rate crisis (Joy, 2011;Reboredo, 2013b;2014a and b;Qureshi et al, 2018;Bedoui et al, 2019). Some studies have also focused on non-crisis uncertainty such as economic uncertainty (Hood andMalik, 2013 andWu et al, 2019), and commodity price shock (Reboredo, 2013a;Salisu and Adeniran, 2020).…”
Section: Motivationmentioning
confidence: 99%
“…It is also interesting to study whether the evidence we have reported in this research extends to markets for other natural resources. In this regard, the link between climate-risk factors and the volatility of movements of prices of important agricultural commodities is particularly important, as might also be the case of precious metals which have been considered as traditional safe-havens in the wake of global risks and uncertainties [57]. We hope that our research will set the stage for such future empirical analyses.…”
Section: Implications For Economic Agentsmentioning
confidence: 93%